2014
DOI: 10.1177/1350650114528317
|View full text |Cite
|
Sign up to set email alerts
|

Large hydrodynamic thrust bearing: Comparison of the calculations and measurements

Abstract: Hydrodynamic thrust bearings, used to carry axial loads in heavily loaded shafts of water power plants hydro turbines, can reach outer diameters even exceeding 5 m. In such large objects scale effect could be observed. According to this, allowable bearing specific load assuring safe operation of the bearings has to be decreased, which increases thrust bearing dimensions. This effect is caused by excessive thermal deflections of bearing pads, which significantly change oil gap geometry, and in consequence, decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 21 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…Detailed description of the model can be found in Refs. [18,19]. The temperature in the lubricated film and in the pad is calculated by solving the 3D energy equation (i.e., the viscosity is varying across the film thickness) and the 3D heat transfer equation, respectively, using the finite difference method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed description of the model can be found in Refs. [18,19]. The temperature in the lubricated film and in the pad is calculated by solving the 3D energy equation (i.e., the viscosity is varying across the film thickness) and the 3D heat transfer equation, respectively, using the finite difference method.…”
Section: Methodsmentioning
confidence: 99%
“…1 Itaipu thrust bearing pad and support arrangement [18]. In previous works [18,19], the authors completed TEHD analysis of Itaipu thrust bearing without including hydrostatic recess. Comparison of predictions and measurements revealed that there were results discrepancy, especially in the vicinity of the hydrostatic recess.…”
Section: Introductionmentioning
confidence: 99%
“…These examples are the results of the testing of a large bearing in a special unique test rig reported by Yuan et al [11]. Other published results of comparisons between calculations and field data were presented by Dąbrowski and Wasilczuk [12], where the object was a hydrogenerator bearing with a system of compensation of thermal deflections; by Wodtke et al [13], where the results of one of the largest thrust bearings in the world, installed in the Itaipu power plant were presented, and the method utilized was FSI (fluid structure interaction) combining a CFD (computational fluid dynamics) solution for a fluid film with a FEM (finite element method) solution for a solid structure. Huang et al [14] published a detailed comparison between the experimental results obtained in a special test rig on a bidirectional bearing and numerical predictions.…”
Section: Introductionmentioning
confidence: 92%
“…Wodtke, Schubert and Fillon diagnosed about the hydrodynamic thrust bearings used to carry axial loads in load shafts of water power hydro turbines could reach aspect of outer diameter even over five meter also enlarged thrust bearing dimensions will decreases their operation capability at once. They couldn't develop suitable agreement between bearings and concerned predictions obtained by using both theoretical models and experiments data [20].…”
Section: Literature Reviewmentioning
confidence: 99%